2018
DOI: 10.18632/oncotarget.24785
|View full text |Cite
|
Sign up to set email alerts
|

Circulating programmed death ligand-1 (cPD-L1) in non-small-cell lung cancer (NSCLC)

Abstract: BackgroundThis study aimed at investigating feasibility of programmed death ligand-1 (PD-L1) testing in plasma samples of advanced NSCLC patients receiving first-line treatment, assessing whether circulating (c)PD-L1 levels were modified by the therapy and whether baseline cPD-L1 levels were associated with patients’ clinical responses and survival outcome.MethodsPeripheral blood samples were collected from 16 healthy volunteers and 56 newly diagnosed NSCLC patients before and at 12th week during the course of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 31 publications
2
21
1
2
Order By: Relevance
“…Vecchiarelli et al [116] 151 melanoma patients sPD-L1 exists as several variants that can originate from both tumor and immune cells sPD-L1 may serve as a practical dynamic biomarker for the prediction of durable efficacy to immunotherapy agents.…”
Section: T-cell Receptor Repertoirementioning
confidence: 99%
“…Vecchiarelli et al [116] 151 melanoma patients sPD-L1 exists as several variants that can originate from both tumor and immune cells sPD-L1 may serve as a practical dynamic biomarker for the prediction of durable efficacy to immunotherapy agents.…”
Section: T-cell Receptor Repertoirementioning
confidence: 99%
“…In order to overcome some of the limits of PD-L1 IHC testing, such as tissue unavailability for molecular testing in up to 30% of NSCLC patients [45] and spatial/temporal heterogeneity of IHC expression [46], some studies evaluated soluble PD-L1 (sPD-L1) or PD-L1 expression in Circulating Tumor Cells (CTCs) as an alternative source for PD-L1 evaluation as well as a dynamic biomarker in patients treated with conventional treatments [47][48][49] and/or ICIs [50][51][52][53][54]. High baseline levels of sPD-L1, assessed by an Enzyme Linked Immunosorbent Assay (ELISA), is a poor prognostic factor in lung cancer and seems associated with lower response to PD-1 blockage [55].…”
Section: Blood Sample Tmb and Pd-l1mentioning
confidence: 99%
“…However, changes of sPD-L1 during ICIs have been associated with conflicting results [54]. Interestingly, some data suggest that first line chemotherapy (e.g., platinum and pemetrexed) could significantly increase sPD-L1 median level from baseline, while targeted therapies do not appear to modify sPD-L1 level [47].…”
Section: Blood Sample Tmb and Pd-l1mentioning
confidence: 99%
“…Recent data described discordant results on the predictive and prognostic significance of sPD-L1 in lung cancer patients [25], and the ability of sPD-L1 to interact with its ligand PD-1 on T cells is still on debate. Nevertheless, PD-L1 plasma levels were significantly enhanced in NSCLC patients receiving standard first-line chemotherapy [8] and our data indicated that pemetrexed, as a single regimen, can increase sPD-L1 in plasma patients.…”
Section: Discussionmentioning
confidence: 52%
“…The regulation of PD-L1 expression is very complex, varying among different tumor types and including both transcriptional and post-transcriptional mechanisms of control [8]. To unravel the mechanisms of pemetrexed-mediated upregulation of PD-L1, we compared the effects of IFN-γ and pemetrexed on intracellular signaling pathways.…”
Section: Pemetrexed-induced Pd-l1 Expression Is Mediated By Mtor and mentioning
confidence: 99%